Mycoplasma haemominutum in the city of Ibague city (Colombia): report of five cases - Mayorga, Daniel (2019)
The aim of this study was to describe a series of cases of hemoplasmosis in domestic cats in the city of Ibagué (Colombia), and the first report of Mycoplasma haemominutum in the country. Blood samples from patients admitted to the outpatient service of the Small Animal Clinic of the University of Tolima were analyzed by conventional PCR for the amplification of the 16s ribosomal gene to obtain a final product of 194 bb. In addition, hematic biometrics and serology were performed for viral diseases (Anigen FIV Ab/FeLV Ag Test kit). The amplicons obtained were subjected to sequencing and bioinformatic analysis (Geneious® 8.1.9). It was found hypochromic normocytic anemia in two cats, leukocytosis in a cat and thrombocytopenia in four of them. Two were seropositive for feline immunodeficiency virus antibodies and feline leukemia virus (FeLV) antigens and one was seropositive for FeLV. Samples showed positive amplification by PCR and revealed 98.7% of identity of 16S ribosomal gene compared with different isolates of M. haemominutum reported in the database. From the authors' knowledge, this is the first report of hemoplasmas in the city of Ibagué and the first report of M. haemominutum in Colombia.